2006
DOI: 10.1158/0008-5472.can-06-0101
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Stress Induces Dimethylated Histone H3 Lysine 9 through Histone Methyltransferase G9a in Mammalian Cells

Abstract: Dimethylated histone H3 lysine 9 (H3K9me2) is a critical epigenetic mark for gene repression and silencing and plays an essential role in embryogenesis and carcinogenesis. Here, we investigated the effects of hypoxic stress on H3K9me2 at both global and gene-specific level. We found that hypoxia increased global H3K9me2 in several mammalian cell lines. This hypoxia-induced H3K9me2 was temporally correlated with an increase in histone methyltransferase G9a protein and enzyme activity. The increase in H3K9me2 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
182
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(195 citation statements)
references
References 45 publications
(58 reference statements)
11
182
1
1
Order By: Relevance
“…Thus, a global decrease in H3K9 acetylation is a possible consequence of hypoxia-induced HDAC upregulation (Johnson et al, 2008). In fact, the H3K9 acetylation reduction occurs by the increase G9a histone methyltransferase expression, which raises global H3K9 methylation, a repressive histone mark (Chen et al, 2006).…”
Section: Hypoxiamentioning
confidence: 99%
“…Thus, a global decrease in H3K9 acetylation is a possible consequence of hypoxia-induced HDAC upregulation (Johnson et al, 2008). In fact, the H3K9 acetylation reduction occurs by the increase G9a histone methyltransferase expression, which raises global H3K9 methylation, a repressive histone mark (Chen et al, 2006).…”
Section: Hypoxiamentioning
confidence: 99%
“…25,28 One potential mechanism of increased H3K9me2 is believed to be mediated by the histone methyltransferase G9a, which has also been shown to increase in hypoxia. 28 In addition to the emerging role of DNA methylation in regulating HIF binding to target genes, it has been shown that hypoxia can itself promote epigenetic changes in cancer cell lines. Using HPLC to quantify the global levels of 5'-methylcytidine in human colorectal and melanoma cell lines, Shahrzad et al demonstrated that exposure to anoxia (≤0.1% oxygen, 24 hours) induces a 15-20% reduction in CpG methylation.…”
Section: The Role Of Epigenetics In Hif-1 Binding and Regulation Of Tmentioning
confidence: 99%
“…Costa and colleagues showed that hypoxia increased H3K9me2, as well as the histone methyltransferase G9a protein and enzyme activity in human lung carcinoma cells. 39 Promoter regions of Mlh1 and Dhfr genes had increased H3K9me2 and decreased expression as a result of the hypoxia. 39 A recent study has shown that hypoxia decreased histone H3 acetylation at the Mlh1 promoter in mouse colon cells and resulted in reduced MLH1 expression at mRNA and protein levels.…”
Section: Ink4amentioning
confidence: 99%
“…39 Promoter regions of Mlh1 and Dhfr genes had increased H3K9me2 and decreased expression as a result of the hypoxia. 39 A recent study has shown that hypoxia decreased histone H3 acetylation at the Mlh1 promoter in mouse colon cells and resulted in reduced MLH1 expression at mRNA and protein levels. 40 Solid tumors undergo angiogenesis to meet the increased demand for oxygen and nutrients.…”
Section: Ink4amentioning
confidence: 99%